Respuesta :
minus lw froom both sides
S-lw=wh+hl
S-lw=h(w+l)
divide both sides by (w+l)
[tex] \frac{S-lw}{w+l} [/tex]=h
S-lw=wh+hl
S-lw=h(w+l)
divide both sides by (w+l)
[tex] \frac{S-lw}{w+l} [/tex]=h
Subtract lw from both sides of the equation to give us,
S - lw = wh + hl
Factor out h from the right hand side of the equation,
S - lw = h(w + l)
Divide both side by (w+ l)
(S - lw) / (w + l) = h
Rearranging,
h = (S - lw) / (w + l)
S - lw = wh + hl
Factor out h from the right hand side of the equation,
S - lw = h(w + l)
Divide both side by (w+ l)
(S - lw) / (w + l) = h
Rearranging,
h = (S - lw) / (w + l)